“Ideologi Pendidikan dalam Profil Lulusan 8 Dimensi: Analisis Wacana Kritis Norman Fairclough terhadap Peraturan Menteri Pendidikan dan Peraturan Departemen Pendidikan Nomor 10 Tahun 2025” - Mahsun; Ahmad Sirulhaq; Saharudin; Irma Setiawan; Yudistira (Mataram University, 2025)
This study analyzes the educational ideology contained in the Minister of Education and Culture Regulation Number 10 of 2025 concerning the 8-Dimensional Graduate Profile using Norman Fairclough's Critical Discourse Analysis (CDA) approach. This approach was chosen to uncover the ideological dimensions and power relations hidden behind the national education policy text. The research data were obtained through a study of official documents, specifically Article 4, which outlines the eight dimensions of the graduate profile. The analysis shows that the document's linguistic structure is both prescriptive and normative, employing lexical patterns that emphasize the formation of ideal subjects with religious, nationalist, and productive characteristics. At the level of discourse practice, this policy reflects state dominance in determining the direction of education, while at the social level, it functions as a tool for reproducing national ideology through the formal education system. These findings indicate the existence of a hybrid ideology that combines conservative values ​​based on morality and religiosity with liberal values ​​based on rationality and creativity. Thus, this policy is not simply a technical guide, but rather an ideological text that demonstrates the dialectic between state control and efforts at intellectual liberation in the Indonesian education system.